Mercury pollution in the Arctic from wildfires: Source attribution for the 2000s - Kumar, Aditya; Wu, Shiliang (Environmental Science & Technology, 2019)
Atmospheric mercury (Hg) is a global environmental pollutant, with wildfire emissions being an important source. There have been growing concerns on Hg contamination in the Arctic region, which is largely attributed to long-range transport from lower latitude regions. In this work, we estimate the contributions of wildfire emissions from various source regions to Hg pollution in the Arctic (66° N to 90° N) using a newly developed global Hg wildfire emissions inventory and an atmospheric chemical transport model (GEOS-Chem). Our results show that global wildfires contribute to about 10% (15 Mg year–1) of the total annual Hg deposition to the Arctic, with the most important source region being Eurasia, which contribute to 5.3% of the total annual Hg deposition followed by Africa (2.5%) and North America (1%). The substantial contributions from the Eurasia region are driven by the strong wildfire activity in the boreal forests. The total wildfire-induced Hg deposition to the Arctic amounts to about one-third of the deposition caused by present-day anthropogenic emissions. We also find that wildfires result in significant Hg deposition to the Arctic across all seasons (winter: 8.3%, spring: 7%, summer: 11%, and fall: 14.6%) with the largest deposition occurring during the boreal fire season. These findings indicate that wildfire is a significant source for Arctic Hg contamination and also demonstrate the importance of boreal forest in the global and regional Hg cycle through the mobilization of sequestered Hg reservoir.